Can ultra-wide field retinal imaging replace colour digital stereoscopy for glaucoma detection?. (2nd January 2018) - Quinn, Nicola B.; Azuara-Blanco, Augusto; Graham, Katie; Hogg, Ruth E.; Young, Ian S.; Kee, Frank
ABSTRACT: Purpose : Ultra-wide field (UWF) retinal imaging (Optomap, Optos plc, Dunfermline, UK) is a novel technique to image the peripheral fundus. The goal of this study was to explore the potential use of UWF imaging to detect glaucoma, and specifically to evaluate the reproducibility of measures of vertical cup-to-disc ratio (VCDR) using ultra-wide field (UWF), and the agreement between UWF and standard colour digital stereoscopy (CDS). Methods : An observational study. From a population-based epidemiological study we selected 100 eyes from 100 consecutive participants who were imaged using both standard CDS and UWF retinal imaging. Estimation of the VCDR using both modalities was made by a masked glaucoma specialist and two masked independent observers. Reliability and agreement between colour digital stereoscopy and the UWF imaging was assessed by Bland-Altman scatterplots. Results : Intra-observer reproducibility of the UWF imaging in estimating VCDRs produced Limits of Agreement (LOA) ranging from −0.13 to 0.1 (mean 0.02) and −0.14 to 0.14 (mean 0.0004) for observer 1 and 2 respectively. Inter-observer reliability between observer 1 and the glaucoma specialist for VCDR measurements using CDS and UWF produced LOA ranging from −0.37 to 0.15 (mean −0.11) and −0.24 to 0.26 (mean 0.0005) respectively. Bland Altman plots produced LOA of −0.16 to 0.20 (mean 0.02) between the two imaging methods for assessing VCDR when carried out by a glaucoma specialist. Conclusion : Grading of UWF imaging has high reproducibility in evaluating VCDR and agreement with stereoscopic optic disc imaging and may be suitable for glaucoma diagnosis in situations where CDS is not available.